2022
DOI: 10.3389/fsurg.2022.915522
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Endoscopic Posterior Lumbar Interbody Fusion with Unilateral Laminotomy for Bilateral Decompression Vs. Open Posterior Lumbar Interbody Fusion for the Treatment of Lumbar Spondylolisthesis

Abstract: BackgroundEndoscopic lumbar interbody fusion is a new technology that is mostly used for single-segment and unilateral lumbar spine surgery. The purpose of this study is to introduce percutaneous endoscopic posterior lumbar interbody fusion (PE-PLIF) with unilateral laminotomy for bilateral decompression (ULBD) for lumbar spondylolisthesis and evaluate the efficacy by comparing it with open posterior lumbar interbody fusion (PLIF).MethodsTwenty-eight patients were enrolled in PE-PLIF with the ULBD group and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…A total of 27 articles were included ( Table 1 ), comprising 953 patients in the Endo-LIF group and 1011 undergoing either Open-LIF ( n = 320) or MIS-LIF ( n = 691). Most studies were cohort studies ( n = 25; 18 being retrospective ( 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ), five prospective ( 31 , 32 , 33 , 34 , 35 ), and two not specified ( 36 , 37 )). A quasi-experimental study ( 38 ) and a RCT ( 39 ) were also included.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 27 articles were included ( Table 1 ), comprising 953 patients in the Endo-LIF group and 1011 undergoing either Open-LIF ( n = 320) or MIS-LIF ( n = 691). Most studies were cohort studies ( n = 25; 18 being retrospective ( 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ), five prospective ( 31 , 32 , 33 , 34 , 35 ), and two not specified ( 36 , 37 )). A quasi-experimental study ( 38 ) and a RCT ( 39 ) were also included.…”
Section: Resultsmentioning
confidence: 99%
“…
Figure 8 Endo-LIF vs MIS-LIF: forest plots with the mean difference for post-operative disability ( 6 , 14 , 15 , 16 , 18 , 21 , 22 , 23 , 29 , 35 , 36 , 38 ).
Figure 9 Endo-LIF vs Open-LIF: forest plots with the mean difference for post-operative disability ( 13 , 19 , 24 , 26 , 31 , 32 , 33 , 37 ).
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 Despite this, endoscopic decompression techniques, which are relatively new, have increased in popularity. 15 Increased utilization of endoscopic procedures can be attributed to the minimally invasive nature of endoscopic procedures. 12 Previous studies comparing open to endoscopic decompression surgery have found fewer surgical complications in the latter cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, less postoperative low back pain compared to other techniques was observed [ 21 ]. The reason for this reduced pain may be due to less surgical trauma [ 24 ], less estimated blood loss [ 29 ], and shorter hospital stay [ 39 ] with ELIF compared to the other surgical techniques.…”
Section: Discussionmentioning
confidence: 99%